Preparation and Characterisation of Some New Polymeric Chelates of Transition Metal Ions - Sarin, I.M.; Juneja, H.D.; Munshi, K.N. (Asian Journal of Chemistry, 2010)
Polymeric complexes of 4,4'-bis-mercaptoacetamide diphenyl(BMAD), 4,4'-bis-mercaptoacetamide-3,3'-dimethyl diphenyl(BMADD) and 4,4' -bis-mercaptopropionamide-3,3' -dimethyldiphenyl (BBMPDD) have been synthesised by the interaction ofthese ligands with transition metal ions, viz., Mn(II), Co(ll), Ni(II),Cu(Il) and Zn(II), under suitable experimental conditions. Theextent of interaction of metal to ligand has been established as[ML]n in case of Mn(II), Cu(II) and Zn(ll) polymers whereas[ML(H2O)2]n in case of Co(ll) and Ni(II) polymers. The compositionwas established on the basis of elemental analysis whileelectronic spectra, magnetic moment, infrared spectral studies andthermogravimetric analysis have been used for the structural aspectsof the chelates. Thermal studies of these polymeric chelates indicatetheir stability up to 380-440°C. All these polymeric chelates werefound to be amorphous and insoluble in almost all organic solventswhich indicates their high polymeric nature.